Generation Z's Response to The Use of Gen.Zas (Electronic Game-based Health Promotion Media) to Prevent Bullying Behavior in Generation Z - Ulfa, Miftakhul; Alfianto, Ahmad Guntur; Kurniyanti, Mizam Ari; Sulaksono, Ari Dwi (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Bullying can lead a mental health issues among Generation Z. Preventive efforts can be implemented using modern technological approaches. Online games are particularly popular among Generation Z and have the potential to influence behavior when played frequently. This study aims to develop an online game Gen.Zas, as a preventive measure against mental health problems caused by bullying. A quantitative and developmental descriptive research design was used. In the first stage, the online game was developed, followed by a perception test in the second stage, conducted with 90 Generation Z respondents from Malang city. Three indicators were evaluated: feasibility of presentation, graphic, and storyline feasibility. The results showed that the perception-test has percentage feasibility score of 86.04% (highly valid and well received) for presentation, 70.74% (valid and feasible) for graphics, and 60.5% (valid and feasible) for the storyline. In conclusion, the Gen.Zas game serves as an educational adventure game that addresses bullying in school environment while incorporating assertiveness techniques to help Generation Z manage bullying behavior effectively.